Strong valence band convergence to enhance thermoelectric performance in PbSe with two chemically independent controls - Luo, Zhong-Zhen (2021)
We present an effective approach to favorably modify the electronic structure of PbSe using Ag doping coupled with SrSe or BaSe alloying. The Ag 4d states make a contribution to in the top of the heavy hole valence band and raise its energy. The Sr and Ba atoms diminish the contribution of Pb 6s2 states and decrease the energy of the light hole valence band. This electronic structure modification increases the density-of-states effective mass, and strongly enhances the thermoelectric performance. Moreover, the Ag-rich nanoscale precipitates, discordant Ag atoms, and Pb/Sr, Pb/Ba point defects in the PbSe matrix work together to reduce the lattice thermal conductivity, resulting a record high average ZTavg of around 0.86 over 400–923 K.